2003
DOI: 10.1086/379896
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Hepatitis B Virus (HBV)–Specific T Cell Responses with Treatment of Human Immunodeficiency Virus/HBV Coinfection

Abstract: Liver-related mortality is an increasing problem in human immunodeficiency virus (HIV)/hepatitis B virus (HBV)-coinfected patients receiving highly active antiretroviral therapy (HAART). In HIV-negative patients, HBV chronicity is associated with a reduction in specific T cell responses that can be partially restored by treatment with lamivudine. We studied 5 HIV/HBV-coinfected patients treated with HAART, either with or without addition of a drug with specific anti-HBV activity. Our data show that reconstitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…A previous immunologic study involving 5 patients coinfected with HIV and HBV found evidence of the reconstitution of a functionally active HBV-specific CD8 cell response when HAART was combined with an anti-HBV drug [14]. More recently [15], the same group demonstrated that an HBV-specific CD8 cell response had been reconstituted in 50% of the HIV-infected patients receiving HAART.…”
Section: Discussionmentioning
confidence: 97%
“…A previous immunologic study involving 5 patients coinfected with HIV and HBV found evidence of the reconstitution of a functionally active HBV-specific CD8 cell response when HAART was combined with an anti-HBV drug [14]. More recently [15], the same group demonstrated that an HBV-specific CD8 cell response had been reconstituted in 50% of the HIV-infected patients receiving HAART.…”
Section: Discussionmentioning
confidence: 97%
“…HBV-specific CD8 T-cell responses recover in patients on ART, but this has not been related to LEE (75,76). A lack of HBV-specific CD4 T-cell help in HIV-HBV-coinfected individuals may lead to an inefficient or dysregulated HBV-specific CD8 T-cell response and/or a greater role for innate immunity (24).…”
Section: Ird May Present As Lee Following Initiation Of Art In Hiv-hbmentioning
confidence: 99%
“…Independent of the use of lamivudine, HAART may induce reconstitution of the adaptive immune response and this is a 'double-edged sword' in patients infected with HBV: on one side, anecdotal reports suggest the induction of HBV seroconversion and therefore a better control of HBV replication with or without flares of necro-inflammatory activity [41][42][43][44]; on the other side, flares of necroinflammatory activity have been reported without modification of HBV markers and of HBV replication levels [45][46][47][48]. However, the incidence of HAART-induced HBsAg seroconversion has not been accurately determined, but occurred in one out of 24 HBsAg-positive patients prospectively followed during HAART in one of the largest published studies [49].…”
Section: Natural History Of Hbv-related Disease In Hiv-infected Patiementioning
confidence: 99%